Twelve-month outcomes of an ab interno gelatin stent combined with cataract surgery or as a standalone procedure in pseudophakic eyes with open-angle glaucoma. Issue 8 (August 2020) - Rather, Peyton A.; Vold, Steven; McFarland, Michael
Abstract : A total of 92 eyes were implanted with the ab interno gelatin stent at a U.S. multisubspecialty ophthalmology practice. At 12 months, most were medication-free with an IOP ≤ 18 mm Hg. Abstract : Purpose: To provide safety and effectiveness outcomes at 12 months postsurgery for an ab interno transscleral gelatin stent in patients with advanced refractory glaucoma or intolerant of medical therapy. Setting: Multisubspecialty ophthalmology practice and surgery center. Design: Retrospective, single-arm, cohort study. Methods: All patients implanted with the gelatin stent either combined with cataract surgery or as a solo procedure between February 2017 and April 2018 and meeting eligibility criteria were included. Outcome measures included proportion of patients achieving a 20% reduction in intraocular pressure (IOP), proportions at or below 12 mm Hg, 15 mm Hg, and 18 mm Hg, IOP, medication usage, needling rate, and adverse events. Results: The study included 92 eyes of 69 patients. Mean preoperative IOP and medications were 16.6 mm Hg on 2.1 medications. Average visual field mean deviation was −13.7 dB. Half (48%) of the patients achieved the primary endpoint of 20% reduction while medication use decreased by −1.7 medications. Most patients at 12 months had IOP of 18 mm Hg or less on zero medications (74%), whereas 34% were medication free and had IOP of 12 mm Hg or less. Bleb needling was required for only 14% of patients. There were few adverse events (13% of eyes), the most common being corrected distance visual acuity loss and hyphema. Conclusions: Eyes with advanced glaucoma despite maximum tolerated medical therapy achieved lower target IOP on fewer medications after implantation with the gelatin microstent.